Functional characterization of a natural retinoic acid responsive element. - Vivanco Ruiz, M M (1991)
Retinoic acid receptor (RAR) and thyroid hormone receptor (T3R) are thought to bind as dimers to a T3 responsive element (T3REpal) comprised of inverted repeats of the half-site motif GGTCA. However, a RA responsive element (beta RARE) was previously identified in the promoter of the RAR beta 2 gene which contains two direct repeats of the motif GTTCA spaced by a six nucleotide gap. We now demonstrate the ability of RAR alpha, beta and gamma to bind to and transactivate through this element and that the two direct repeats comprise the beta RARE. Surprisingly, the GTTCA motifs rearranged to form a palindrome do not confer RA responsiveness to a heterologous promoter. Furthermore, no significant level of transactivation is detected by ligand-activated RAR through the Moloney murine leukaemia virus T3RE, which comprises two direct repeats of the sequence GGTCA/C spaced by a five nucleotide gap. Similarly, T3R does not induce gene expression through the beta RARE. This study establishes the preference of T3R to transactivate through direct repeats spaced by a five nucleotide gap as opposed to a six nucleotide gap. In contrast, RAR appears to be more flexible with respect to spacing requirements between repeats, although higher levels of transactivation are obtained through direct repeats spaced by a six nucleotide gap. Interestingly, although some elements mediate either RA or T3 induction, changing a single nucleotide in the MoMLV T3RE with a five nucleotide spacing creates a promiscuous RA/T3 responsive element.